2016
DOI: 10.1071/en14229
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on arsenosugars and arsenolipids in Ectocarpus (Phaeophyta)

Abstract: Environmental context. Arsenolipids, which are present in seaweed, can show high toxicity, emphasising the need for more information on these compounds. We investigated the effects of different stress factors on the arsenic compounds formed by cultures of brown algae, and compared the results with those from field-collected samples. We show that the arsenolipid and arsenosugar profiles differ depending on the experimental conditions, and that a deficiency in phosphate has a direct positive effect on the biosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…A residual, non-extractable fraction often remains following speciation analysis, and can contain a significant proportion of total As in some samples (Leufroy et al 2012, Petursdottir et al 2016). The form of As in this fraction remains unclear.…”
Section: Sources and Distribution Of Organic As Species In Marine mentioning
confidence: 99%
See 1 more Smart Citation
“…A residual, non-extractable fraction often remains following speciation analysis, and can contain a significant proportion of total As in some samples (Leufroy et al 2012, Petursdottir et al 2016). The form of As in this fraction remains unclear.…”
Section: Sources and Distribution Of Organic As Species In Marine mentioning
confidence: 99%
“…The form of As in this fraction remains unclear. Seaweeds can contain variable amounts of un-extractable or residual As (Lai et al 1998, Raab et al 2005, van Elteren et al 2007, Petursdottir et al 2016), which is thought to be bound to thiol-containing structural compounds (Thomson et al 2007). Molluscs frequently have high levels of residual As (8–58%; (Fricke et al 2004, Whaley-Martin et al 2012, Berges-Tiznado et al 2013)), and while As in crustaceans is mostly water soluble, the residual fraction can also be significant (9–17% (Li et al 2003)).…”
Section: Sources and Distribution Of Organic As Species In Marine mentioning
confidence: 99%
“…Several studies have contributed to our understanding of the occurrence of arsenolipids [16][17][18][19][20][21][22], but we still have only limited knowledge about the metabolism of these compounds and their behavior in natural systems. In this regard, two recent studies by Glabonjat et al [19,22] have revealed the likely significance of phytyl 2-O-methyl arsenosugars in the natural cycling of arsenic.…”
Section: Introductionmentioning
confidence: 99%
“…Despite arsenic-containing lipids (arsenolipids; the major classes are depicted in Fig. S1) originally being identified over 30 years ago by Morita and Shibata (1988), far less information exists on the production and biosynthesis of arsenolipid species by marine organisms (Sele et al 2012;Amayo et al 2014;Petursdottir et al 2015;Glabonjat et al 2018). In recent years, however, there has been renewed interest in the characterization of arsenolipids in marine organisms; and as a result, over 80 arsenolipids including As-hydrocarbons (AsHCs) (Taleshi et al 2008), As-fatty acids (Rumpler et al 2008), As-fatty alcohols (Amayo et al 2013), As-phospholipids (AsPLs) (Morita and Shibata 1988;Viczek et al 2016), and methoxy As-sugar phytol (Glabonjat et al 2017) have been identified from a range of organisms such as marine algae, squid, and fish.…”
Section: Introductionmentioning
confidence: 99%